The Influence Of Czech Herbal Medicine In Increasing Appetite On Toddlers - Malati Esti Putri; Dian Priharja Putri (CV. Inara, 2023)
Difficulty eating in children is still a complaint from parents. Toddlers often experience a decrease in appetite which results in reduced nutritional intake resulting in decreased body weight. This can result in decreased immune system, impaired brain function which can cause disability and death. According to the World Health Organization, in 2013 there were 99 million children under five in the world suffering from malnutrition and 67% were in Asia. There are 17 thousand deaths every day due to nutritional problems and infectious diseases. In Indonesia, especially the Javanese, believe that herbal medicine has the property of increasing appetite in children. Research Objectives To determine the effect of herbal medicine in increasing appetite in toddlers 12-36 months. Pre-experimental designs with one group pretest-posttest. The sampling technique was total sampling, namely 10 toddlers or all toddlers aged 12-36 months in the Panggarangan Health Center area with decreased appetite problems in November 2022. Appetite assessment results before being given herbal medicine to 10 respondents with a minimum score of 2 and a maximum of 5, and an average of 3.70 (SD 0.949). While the appetite after being given herbal medicine with a minimum value of 7 and a maximum of 10, and an average of 8.70 (SD 1.059). So, herbal medicine has the effect of increasing appetite in toddlers aged 12-36 months in the Penggarangan Health Center (p-value <0.000). Herbal medicine has an effect on increasing appetite in toddlers 12-36 months. It is hoped that the public can be more selective in choosing ingredients and herbal medicine providers to increase toddlers' appetite.